2010
DOI: 10.1371/journal.pone.0008882
|View full text |Cite
|
Sign up to set email alerts
|

A Photoprotein in Mouse Embryonic Stem Cells Measures Ca2+ Mobilization in Cells and in Animals

Abstract: Exogenous expression of pharmacological targets in transformed cell lines has been the traditional platform for high throughput screening of small molecules. However, exogenous expression in these cells is limited by aberrant dosage, or its toxicity, the potential lack of interaction partners, and alterations to physiology due to transformation itself. Instead, primary cells or cells differentiated from precursors are more physiological, but less amenable to exogenous expression of reporter systems. To overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Recently, mouse embryonic stem cells were engineered to express a Ca 2+ -sensitive protein, and HA was used to select clones that augmented [Ca 2+ ] i , confirming the presence of histaminergic G-protein coupled receptors in pluripotent stem cells. Furthermore, neural differentiation of these embryonic stem cells rendered cells that also were able to increase [Ca 2+ ] i after addition of 100 μM HA; all these effects were mediated by H 1 R [31], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, mouse embryonic stem cells were engineered to express a Ca 2+ -sensitive protein, and HA was used to select clones that augmented [Ca 2+ ] i , confirming the presence of histaminergic G-protein coupled receptors in pluripotent stem cells. Furthermore, neural differentiation of these embryonic stem cells rendered cells that also were able to increase [Ca 2+ ] i after addition of 100 μM HA; all these effects were mediated by H 1 R [31], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…We recently described the generation of PhotoTopo mice (Cainarca et al 2010). Briefly, c‐Photina – a photoprotein derived from Clytin ( Clytia gregaria ) and modified by random mutagenesis – was optimized for mammalian codon usage and fused to a mitochondrial tag (human cytochrome C oxidase, subunit VIII).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we establish a live‐cell bioluminescence [Ca 2+ ] m imaging approach that overcomes these limitations without compromising its numerous advantages. Using genetically engineered PhotoTopo mice that ubiquitously express the optically improved photoprotein c‐Photina within the mitochondrial matrix (Cainarca et al 2010) and a dedicated bioluminescence microscope, we record (sub)cellular mitochondrial Ca 2+ signals at millisecond resolution. Combining both [Ca 2+ ] m and [Ca 2+ ] c imaging methods with whole‐cell patch‐clamp recordings, we describe here the key components of a Ca 2+ mobilization network that underlies purinergic signalling in primary mouse Sertoli cells.…”
Section: Introductionmentioning
confidence: 99%
“…A mES cell line expressing a Ca2 + −activated photoprotein as a reporter gene under the control of a ubiquitous promoter was generated [63]. Differentiating the cPhotina mES cell line into neuronal cells, it was demonstrated that this system is sensitive enough to study the pharmacological modulation of target genes that induce Ca2+ mobilization.…”
Section: Pluripotency and Self-renewalmentioning
confidence: 99%